2021
DOI: 10.1021/acs.chemmater.1c00107
|View full text |Cite
|
Sign up to set email alerts
|

The Elusive Structure of Magadiite, Solved by 3D Electron Diffraction and Model Building

Abstract: In addition to a great swelling ability, layered silicates also allow the functionalization of their interlayer region to form various robust green materials that are used as CO 2 adsorbents, drug carriers, or catalysts. Here, the unique magadiite structure, which has resisted elucidation despite many attempts and applications the material offers, is finally described. A materialspecific strategy allowed the use of 3D electron diffraction which led to the success of deciphering the atomic structure. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 88 publications
3
31
0
Order By: Relevance
“…Whereas 1 H NMR results would suggest that this is the interlayer water signal, which disappears above temperatures higher than 400 °C, 2 H NMR shows the presence of these species even at higher temperatures, pointing out to SiOD groups with high mobility. The structure of magadiite was recently discussed by Krysiak et al They used 3D electron diffraction and model building to solve the magadiite structure of Na- and NH 4 -magadiite. In their structure models, there are only OH groups located on the interface between the tetrahedral silicate layer and the interlayer.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Whereas 1 H NMR results would suggest that this is the interlayer water signal, which disappears above temperatures higher than 400 °C, 2 H NMR shows the presence of these species even at higher temperatures, pointing out to SiOD groups with high mobility. The structure of magadiite was recently discussed by Krysiak et al They used 3D electron diffraction and model building to solve the magadiite structure of Na- and NH 4 -magadiite. In their structure models, there are only OH groups located on the interface between the tetrahedral silicate layer and the interlayer.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[41,51] Nevertheless, especially in hybrid layered systems, besides beam sensitivity, stacking disorder is another difficulty that often requires a combination of several methods such as 3D ED, PXRD, modeling/simulation, and DFT calculations. [41,52] The solid phases of [FcC 2 Br] Pb and [FcC 4 Br] Pb have been investigated with 3D ED, resulting in the composition (FcC 2 ) PbBr 3 and (FcC 4 ) 4 Pb 3 Br 10 , respectively. The crystallographic details of all three phases are summarized in Figure 2 and Table 1 and will be discussed here in detail.…”
Section: Synthesis Of Ferrovskites and Crystal Structure Determinatio...mentioning
confidence: 99%
“…It could be shown that the development of fast acquisition protocols [45,50] allows the use of this technique with various transmission electron microscopes (TEMs) even for very beam sensitive materials. [41,51] Nevertheless, especially in hybrid layered systems, besides beam sensitivity, stacking disorder is another difficulty that often requires a combination of several methods such as 3D ED, PXRD, modeling/simulation, and DFT calculations. [41,52] The solid phases of [FcC 2 Br] Pb and [FcC 4 Br] Pb have been investigated with 3D ED, resulting in the composition (FcC 2 ) PbBr 3 and (FcC 4 ) 4 Pb 3 Br 10 , respectively.…”
Section: Synthesis Of Ferrovskites and Crystal Structure Determinatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Earth sciences, 3D ED has been used for the structure elucidation of nanoscopic inclusions (Xiong et al , 2020), mineral seeds (Németh et al , 2018), hydrated phases (Mugnaioli et al , 2020a; Krysiak et al , 2021) and modulated systems (Lanza et al , 2019; Steciuk et al , 2020), even when characterised by very large asymmetric units (Rozhdestvenskaya et al , 2010; Mugnaioli et al , 2020b). 3D ED has been applied to geological samples in different contexts (Mugnaioli and Gemmi, 2018), and in particular for the characterisation of meteorites (Pignatelli et al , 2017, 2018; Suttle et al , 2021), impactites (Campanale et al , 2021), cryptocrystalline oxides (Koch-Müller et al , 2014) and hydroxides (Viti et al , 2016).…”
Section: This Workmentioning
confidence: 99%